Development of an ESD-Based Electronic Module on the Topic of Biogas Purification from Organic Waste to Train Students' Scientific Literacy: Pengembangan Modul Elektronik Berbasis ESD pada topik Pemurnian Biogas dari Limbah Organik untuk Melatih Literasi Sains Murid - Muhammad Rizal Syihabuddin Rizal; Ali Kusrijadi; Atep Rian Nurhadi (Jurnal Pendidikan dan Pembelajaran Kimia, 2026)
Development of an ESD-Based Electronic Module on the Topic of Biogas Purification from Organic Waste to Train Students' Scientific Literacy. This study aims to develop a product in the form of an ESD-based e-module on the topic of biogas purification from organic waste to train students' scientific literacy. The research method used is Design and Development Research (DDR) type 1 with a focus on specific project phases that include the analysis, design, development, and evaluation stages. This study involved seven chemistry teachers in the initial needs analysis stage, three validators consisting of two expert lecturers and one chemistry teacher, and nine grade XI students at a high school in Bandung City for a limited trial at the evaluation stage. Data collection instruments were carried out using e-module validation sheets, e-module questions, and analysis of student answers. The validation results showed that the developed e-module met the e-module eligibility criteria with several suggestions and improvements from the validators. In addition, the results of the limited trial on the achievement of students' scientific literacy profiles showed a good level of achievement based on the average value of the three aspects of scientific literacy, so this e-module has the potential to train students' scientific literacy in chemistry learning.